Correlation between Demographics, Clinical and Risk Factors for HIV Infection with HIV/TB Co‑infection in Amertha Clinic Kerti Praja Foundation Denpasar - Yuneti Octavianus Nyoko; I Wayan Gede Artawan Eka Putra; Anak Agung Sagung Sawitri (Public Health and Preventive Medicine Archive, 2014)
Background and purpose: HIV infection increases the risk of developing tuberculosis (TB), as TB infection increases the progression of HIV. In Bali, HIV/TB co-infected patients have increased from 26% in 2012 to 30% in 2013. Study on factors related with the occurrence of HIV/TB co-infection is limited in Indonesia. This study aims to determine the correlation between demographics, clinical and risk factors for HIV infection with HIV/TB co-infection in Amertha ClinicKerti Praja Foundation Bali.Methods: The study design was cross-sectional using secondary data of patients with HIV/AIDS who were receiving antiretroviral therapy (ART) from 2002-2012. Independent variables were demographics: gender, age, education level, working status, and presence of ART supervisor; clinical: hemoglobin count, weight, CD4 count; and risk factor for HIV infected. The status of HIV/TB co-infection was the dependent variable. Data was analysed using univariate, bivariate (chi-square) and multivariate (cox regression).Results: From the 531 patients, the majority were male (57.6%) and aged ≥31 years (50.8%). About 5.5% of patients experienced HIV/TB coinfection. Multivariate analysis indicated that the variables correlating with HIV/TB co-infection occurrence were CD4 count at baseline ≤200 cell/mm3 (PR=10.34; 95%CI: 1.39-76.69; p=0.022) and risk factor for HIV infected with IDU (PR=3.27; 95%CI: 1.56-6.88; p=0.002).Conclusion: Patients with CD4 count ≤200 cell/mm3 and HIV infected by IDU have correlating with HIV/TB co-infection.